Observation of indirect ionization of W7+ in EBIT plasma. Issue 13 (January 2020) - Lu, Q; He, J; Tian, H; Li, M; Yang, Y; Yao, K; Chen, C; Xiao, J; Li, J G; Tu, B; Zou, Y
Synopsis: In this work, visible and EUV spectra of W 7+ have been measured using the high-temperature super-conducting electron-beam ion trap at the Shanghai EBIT laboratory under extremely low-energy conditions. The relevant atomic structure has been calculated by using the flexible atomic code package and the GRASP2K code. A hypothesis for the charge-state evolution of W 7+ is proposed based on our results. The occurrence of W 7+ ions results from indirect ionization caused by stepwise excitation between some metastable states of lower-charge-state W ions, at the nominal electron beam energy of 59 eV.